Increase in IS256 transposition in invasive vancomycin heteroresistant Staphylococcus aureus isolate belonging to ST100 and its derived VISA mutants - Di Gregorio, Sabrina Noelia (2016)
In Staphylococcus aureus, transposition of IS256 has been described to play an important role in biofilm formation and antibiotic resistance. This study describes the molecular characterization of two clinical heterogeneous vancomycin-intermediate S. aureus (hVISA) isolates recovered from the same patient (before and after antibiotic treatment) and two VISA derivatives obtained by serial passages in the presence of vancomycin. Our results showed that antibiotic treatment (in vivo and in vitro) could enhance IS256 transposition, being responsible for the eventual loss of agr function. As far as we know this is the first study that reports the increase of IS256 transposition in isogenic strains after antibiotic treatment in a clinical setting.